Basalt-Hosted Microbial Communities in the Subsurface of the Young Volcanic Island of Surtsey, Iceland - Bergsten, Pauline; Vannier, Pauline; Klonowski, Alexandra María; Knobloch, Stephen; Gudmundsson, Magnús Tumi; Jackson, Marie Dolores; Marteinsson, Viggó Thor (Frontiers in Microbiology, 2021)
The island of Surtsey was formed in 1963–1967 on the offshore Icelandic volcanic rift zone. It offers a unique opportunity to study the subsurface biosphere in newly formed oceanic crust and an associated hydrothermal-seawater system, whose maximum temperature is above 120°C at about 100 m below surface. Here we present new insights into the diversity, distribution and abundance of microorganisms in the subsurface of the island, 50 years after its creation. Samples, including basaltic tuff drill cores and associated fluids acquired at successive depths as well as surface fumes from fumaroles, were collected during the expedition 5059 of the International Continental Scientific Drilling Program (ICDP) specifically designed to collect microbiological samples. Results of this microbial survey are investigated with 16S rRNA gene amplicon sequencing and Scanning Electronic Microscopy (SEM). To distinguish endemic microbial taxa of subsurface rocks from potential contaminants present in the drilling fluid, we use both methodological and computational strategies. Our 16S rRNA gene analysis results expose diverse and distinct microbial communities in the drill cores and the borehole fluid samples, which harbor thermophiles in high abundance. Whereas some taxonomic lineages detected across these habitats remain uncharacterized (e.g., Acetothermiia, Ammonifexales), our results highlight potential residents of the subsurface that could be identified at lower taxonomic rank such as Thermaerobacter, BRH-c8a (Desulfallas-Sporotomaculum), Thioalkalimicrobium and Sulfurospirillum. Microscopy images reveal possible biotic structures attached to the basaltic substrate. Finally, microbial colonization of the newly formed basaltic crust and the metabolic potential are discussed on the basis of the data.